O nome de marca : análise empírica da palvra e da forma - Mendonça, Maria Catarina Miranda Toscano de, 1992- (2016)
This dissertation addresses the historical evolution of some of the leading and most renowned global brands, regarding the changes occurred in their names and subsequent redesigned wordmarks. The work has basically two parts. In the first section some relevant concepts to the topic under study are framed within a literature review. In the latter part an empirical study of exploratory nature is undertaken based on a convenience sample of twenty brands. The study analyzes the main naming and typographic features of brands individually, and then compares the most significant differences found between the late 20th century and the 2000s. The findings suggest that brands adjust their verbal and graphic forms to the characteristics imposed by the current communication paradigm. From the 2000s, brand names became shorter in number of words and also in number of characters. On the other hand, it is also noted that wordmarks assume similar features, causing a typographical standardization ofbrands. As a result, names play a greater role in the identification of the brand, becomingits main source of differentiation. This study covers a not necessarily representative fraction of the numerous existing brands, thus the drawn conclusions should be regarded with some caution. Nonetheless, the observed trend leads to the belief that the results may be extrapolated, although carefully. This research highlights that the selection of a solid name and wordmark is a key investment to any brand. Through these two elements, an organization can successfully communicate the desired image, thereby gaining notoriety and recognition among its preferred audience